Parameter Optimization, Morphological and Histological Characteristics of Accurate Bone Ablation by Femtosecond Laser: An In Vitro Study - Yiyang Wang; Shanshan Liang; Yongsheng Zhou; Fusong Yuan; Hongqiang Ye (Bioengineering)
The use of femtosecond laser for bone ablation has been demonstrated in numerous studies; however, the clinical application requires further optimization to meet safety, accuracy, and efficiency standards. This study aims to optimize the energy density parameter of a robot-controlled femtosecond laser surgical system for bone ablation by assessing temperature changes, ablation efficiency, and ablation effects. Furthermore, the morphological and histological characteristics of bone tissue were compared with those of conventional mechanical methods. The results indicated that a laser energy density of 1.05 J/cm2 was optimal for bone ablation, maintaining the bone surface temperature below 47 °C and achieving an ablation efficiency of 0.145 mm3/s. The deviations in cavity diameters were significantly smaller for the laser group (6.58 ± 18.09 μm) compared to the bur group (80.09 ± 45.45 μm, p < 0.001, N = 5 per group). Femtosecond laser ablation produced cleaner cavity margins with minimal bone debris accumulation. Additionally, the adjacent Volkmann and Haversian canals retained their normal morphology, indicating limited mechanical and thermal damage to the bone tissue. The robot-controlled femtosecond laser system demonstrated the potential for achieving safe, accurate, efficient, and clean bone ablation, offering promising prospects for clinical applications.